Effect of ionic strength on whey protein separation in high performance tangential flow filtration - Muhammad Fakhrullah, Mohd Nor (2010)
High performance tangential flow filtration (HPTFF) is an emerging technology developed from the conventional cross flow filtration (CFF). HPTFF could separate protein components that differ less than three fold in size compared to the CFF, which only applicable to separate the protein components that differ more than tenfold in size. In the current study, HPTFF was operated using PES membrane with MWCO of 30kDa to separate whey protein components into two fractions which is enriched in α-lactalbumin (α-lac) on the permeate side and β-lactoglobulin (β-lg) in the retentate side. In order to get higher permeate value of α-lac, ionic strength of the solution from 0M to 0.5M in HPTFF was studied in this study. The best separation factor was observed at intermediate salt concentration of 0.125M concentration.